Investigation of structure and mechanical properties of plasma vapor deposited nanocomposite TiBN films - 韩滨 D NEENA 王泽松 K K KONDAMAREDDY 李娜 左文彬 闫少健 刘传胜 付德君 (Plasma science & technology, 2017)
TiBN coatings have huge potential applications as they have excellent properties with increasing modem industrial requirements.Nanocomposite TiBN coatings were synthesized on cemented carbide,high speed steel and Si substrates by using cathodic arc plasma ion plating from pure TiB2 ceramic targets.The structure and mechanical properties of the TiBN coatings were significantly influenced by the nitrogen partial pressure.Rutherford backscattering spectrometry demonstrates that the nitrogen content of the coating varied from 2.8% to 34.5% and highresolution electron microscopy images reveal that all coatings have the characteristic of nanocrystals embedded in an amorphous matrix.The root-mean-square roughness of the coatings increases from 3.73 to 14.64 nm and the coefficients of friction of the coatings at room temperature vary from 0.54 to 0.73 with increasing nitrogen partial pressure.The microhardness of the coating increases up to 35.7 GPa at 10 sccm N2 flow rate.The smallest wear rate is 2.65 ×10^-15m^3N^-1m^-1 which indicates that TiBN coatings have excellent wear resistance.The adhesion test revealed that the TiBN coatings have good adhesion at low nitrogen partial pressure.